IMPROVING MOTIVATION IN BUILDING PHOTOPRENEUR CHARACTERISTICS - Sofyandi, Herman; Oktafien, Shinta; Hapsari, Ayuningtyas Y.; Ramadhan, Nabilah; Agustriyana, Darwis (CENTRAL ASIA AND THE CAUCASUS, 2022)
Until now, it is still rare to find people who want to start their life when they graduate from school or college by becoming an entrepreneur. Generally, graduates who have successfully completed their education prefer to be able to immediately work in a company compared to working independently or starting their own business. In fact, graduates should be more encouraged to dare to try entrepreneurship, one of which is to become a Fotopreneur. The so-called Fotopreneur is a photographer or videographer who has an entrepreneurial spirit.Due to the still enactment of restrictions on community activities caused by the outbreak of the Covid-19 virus in Indonesia, especially what happened in the city of Bandung and its surroundings, the Community Service event held this time was still carried out virtually (online) using the Zoom application. To avoid saturation of the participants in participating in this PkM activity, the program does not only contain the presentation of material presented by the resource persons, but the program is combined with a talk show style, so that the program can become more interesting and interactive.When viewed from the number of participants, the material presented and the objectives of the activities to be achieved, it can be said that the PkM activities that have been carried out have been able to achieve the expected targets. By holding this PkM event, it is hoped that the participants who follow it can understand well about what photography is which can be one of the opportunities in business, so that it raises the interest of the participants to become a photopreneur.